Enhancing Pre-Service Physical Education Teachers’ Knowledge through Curriculum-Aligned PETE Lessons in Cambodia - Otomo, Koki; Teraoka, Eishin; Vibol, Deian; Vannphorn, Socheata; Okade, Yoshinori (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2025)
Purpose: To examine the learnability of pre-service teachers’ Specialized Content Knowledge (SCK) related to physical fitness within a brief, curriculum-aligned lesson in Cambodia’s Physical Education Teacher Education (PETE) program. Method: Two 120-minute fitness lessons, aligned with the national secondary PE curriculum, were delivered at the National Institute of Physical Education and Sport (NIPES). Twenty-five candidates participated; analyses included 21 who completed all four administrations (Tests 1–4) of a seven-item Understanding level SCK knowledge test, which required selection of both the correct method and its rationale. In addition, all participants completed the Formative Lesson Assessment. Repeated-measures ANOVA examined baseline stability and intervention effects. Results: Knowledge scores showed no baseline change (Test 1–Test 2) significant pre- to post-lesson improvements, showing a large effect (F(3, 60) = 9.754, p < .001, partial η² = .328); Formative Lesson Assessment ratings were consistently high. Conclusion: In this intervention, a curriculum-aligned short lesson strengthened SCK for balance exercises and helped translate written curriculum aims into learned outcomes in a low-resource PETE setting, thereby providing practice-based evidence to inform teacher preparation in physical education. Given the intentionally brief, blueprint-sampled instrument and single-cohort design, inferences should be considered bounded to this cohort and instrument; broader generalization awaits further validation.